Tren Penggunaan Media Sosial Sebagai Sumber Informasi Politik di Kalangan Generasi Muda Pekanbaru - Dafrizal Samsudin; Indah Mardini Putri; Ramon Zamora (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
The development of communication technology has an impact on access to political information. Social media plays an important role as a source of political information, especially for the younger generation. This research aims to look at trends in the use of social media as a source of political information among the young generation of Pekanbaru. This research uses a quantitative descriptive approach. Data was obtained through a survey by distributing questionnaires to 400 respondents aged 15-24 years. The results of this research show that the young generation of women aged 19-26 years use Instagram, WhatsApp, Twitter, Telegram, Line and Tik Tok, where the locations where they access social media include at home, boarding house, wifi corner and office. The average duration for the younger generation to access social media to search for political information is 5-15 minutes, followed by 26-35 minutes, 46-60 minutes, and >1 hour. On the other hand, the younger generation of men, especially those aged 15-18 years, prefer to use social media Facebook and YouTube as sources of political information, with places to access them being campuses/schools and cafes with an access duration of 15-18 years. 16-25 minutes. The number of young people who access social media for 36-45 minutes tends to be balanced between men and women. Thus, it can be concluded that social media plays an important role as the main channel of political information for the younger generation in the digital era.